Pots Speak Volumes: Commensal Politics and Kitchenwares in Early Horizon Nepeña, Peru. (2nd January 2020) - Sutherland, Kenneth; Chicoine, David; Helmer, Matthew; Ikehara, Hugo C.
Abstract : This contribution examines feasting strategies in Early Horizon Nepeña (800–200 BC), coastal Ancash, north-central Peru. Through the analysis of volumetric capacities of vessels, we estimate scales of food and drink production at three coeval sites of Caylán, Huambacho, and Samanco. Production scales at those communities are used as proxies for domestic economies, their prosperity and ability to sponsor feasts. We compare and analyze scales of domestic production in light of the complex relationships between the different settlements, including variations in their overall functions and place within regional geopolitics. Results shed light on variations in scales of potential commensal hospitality, size of feasting events, and amplitude of commensal communities. The study informs on foodways in incipient urban contexts and suggests economic asymmetries between households from different settlements. We hypothesize that differences between the three sites shaped local politics and played significant roles in the trajectory of the Early Horizon system.